2019
DOI: 10.1016/j.geoderma.2019.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of a Late Quaternary loess-paleosol sequence in central Argentina: Implications for weathering, sedimentary recycling and provenance

Abstract: A loess-paleosol sequence in the Pampean Plain, central Argentina was analyzed geochemically, in order to evaluate the weathering signature and sedimentary recycling as well as to analyze the origin of these loessic sediments. Corralito I sequence is composed of three paleosols and a buried soil separated by loess layers. The loess-paleosol sequence shows a similar geochemical composition throughout, suggesting that pedogenesis has not been intense enough to mask the chemical signature of the parent material. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Its application has enabled for example to distinguish dust sources of the Chinese Loess Plateau and loess deposits in southern China (Hao et al, 2010) and to exclude local sources for aeolian silt mantles on the Californian Channel Islands (Muhs et al, 2007(Muhs et al, , 2008. Campodonico et al (2019) confirmed the dominance of Andean detritus as source material for Pampean loess deposits of Central Argentina, based on bulk geochemical evidence.…”
Section: Sampling and Laboratory Analyses Methodological Background Omentioning
confidence: 93%
“…Its application has enabled for example to distinguish dust sources of the Chinese Loess Plateau and loess deposits in southern China (Hao et al, 2010) and to exclude local sources for aeolian silt mantles on the Californian Channel Islands (Muhs et al, 2007(Muhs et al, , 2008. Campodonico et al (2019) confirmed the dominance of Andean detritus as source material for Pampean loess deposits of Central Argentina, based on bulk geochemical evidence.…”
Section: Sampling and Laboratory Analyses Methodological Background Omentioning
confidence: 93%
“…5 ) 50 . Likewise the potential source areas of the Armenian loess exhibit high χ lf values suggesting that the parent material of the Armenian loess is not comparable to that of loess common in SE Europe or China, but is strongly affected by weathered volcanogenic minerals as it is known from the vast loess areas of Argentina and southern Brazil 51 , 52 . The high magnetic susceptibility (MS) in LPS of NE-Armenia may relate to high proportions of metallic ores within volcanic glasses that attain background levels of up to 20% within unaltered loess 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Ratios of non‐mobile elements in the studied sediments and comparison with regional low‐Ti basalts (based on Bellieni et al ., 1984, Peate, 1997, Kirstein et al ., 2000, Marsh et al ., 2001, Iacumin et al ., 2003, Ewart et al ., 2004, and Hartmann et al ., 2013) and loess sequences at similar latitude (based on Pasquini et al ., 2017 and Campodonico et al ., 2019). …”
Section: Methodsmentioning
confidence: 99%